DELIVERY PERFORMANCE AND SALES TURNOVER OF SMALL AND MEDIUM SIZE EXPORTING FIRMS IN SOUTH-SOUTH, NIGERIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2018)
The study investigated the relationship between delivery performance and sales turnover of food and beverage exporting Small and Medium Enterprises (SMEs) firms in South-South, Nigeria. The study adopted descriptive survey research design, with the questionnaire as the instrument for primary data collection from a population 160 firms involved in exporting food and beverages. A copy of the questionnaire was administered to the sample made up of managers and owners of  the  firms. The questionnaire was validated by experts while the reliability test result using Cronbach Alpha produced a value of  0.913.  Both descriptive and inferential statistical tools were employed to analyze the data with  SPSS (version 21.0).  The statistical result showed that, delivery performance had positive and significant relationship with sales turnover. The study concluded that delivery performance enhances sales performance in terms of sales turnover of food and beverage exporting SMEs in Nigeria. Therefore, this study that recommended entrepreneurs should put in place a sound system and process that will ensure timely delivery of products and services as this would enhance customer satisfaction and improve sales performance.